Black Grass Jelly (Mesona Palustris Bl) Effervescent Powder has Anti-Dyslipidemia in High Cholesterol Diet-Fed Rats and Antioxidant Activity - Dian Handayani; Tri Dewanti Widyaningsih; Novita Wijayanti; Mey Etika (Research Journal of Life Science, 2017)
Dyslipidemia that could be affected by hypercholesterol diet is a contributing factor in millions of deaths worldwide and a risk factor for ischemic heart disease and stroke. High soluble fiber diet is used as one of the non-pharmacological treatments to control hypercholesterolemia. Black Grass Jelly (Mesona palustris BL) also known as black cincau has a high soluble fiber content. This study aimed to investigate the effect of black cincau as effervescent powder form (BCEP) for anti-dyslipidemia and also the antioxidant activity. BCEP was orally administered to twenty male dyslipidemia Wistar rats induced with hypercholesterol diet for 3 weeks then plasma lipid profile was measured using enzymatic CHOD-PAP assay. The antioxidant activity also has been identified. Oral administration of 3 different doses of BCEP resulted in lipid profiles by decreasing plasma cholesterol (TC), triacylglycerol (TG), low-density lipoprotein (LDL), and also high-density lipoprotein (HDL) in dyslipidemia rats (α =  0.01). The increasing doses of BCEP revealed that it has a potential effect of decreasing plasma lipid.